SARS-CoV-2 detection in formalin-fixed paraffin-embedded tissue specimens from surgical resection of tongue squamous cell carcinoma. Issue 11 (4th May 2020) - Guerini-Rocco, Elena; Taormina, Sergio Vincenzo; Vacirca, Davide; Ranghiero, Alberto; Rappa, Alessandra; Fumagalli, Caterina; Maffini, Fausto; Rampinelli, Cristiano; Galetta, Domenico; Tagliabue, Marta; Ansarin, Mohssen; Barberis, Massimo
Abstract : In the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, pathologists can be exposed to infection handling surgical specimens. Guidelines related to safety procedures in the laboratory have been released. However, there is a lack of studies performed on biopsy and surgical resection specimens. Here we report the detection of SARS-CoV-2 in formalin-fixed paraffin-embedded samples from surgical resection of tongue squamous cell carcinoma of a patient who developed COVID-19 postsurgery. RNA of SARS-CoV-2 strain was detected in the tumour and the normal submandibular gland samples using real-time PCR-based assay. No viral RNA was found in metastatic and reactive lymph nodes. We demonstrated that SARS-CoV-2 RNA can be detected in routine histopathological samples even before COVID-19 disease development. These findings may give important information on the possible sites of infection or virus reservoir, and highlight the necessity of proper handling and fixation before sample processing.